ANALYSIS OF FACTORS INFLUENCING STUDENTS' LEARNING MOTIVATION IN THE DIGITAL ERA - Tito Yudistira (EDU RESEARCH, 2025)
This study aims to analyze the factors that influence students' learning motivation in the digital era. In the context of education that is increasingly influenced by technology, it is important to understand how elements such as access to technology, social interaction, and learning environment can affect students' motivation. The research method used is quantitative with data collection through questionnaires distributed to students in several high schools. Data analysis was carried out using descriptive and inferential statistical techniques. The results of the study indicate that access to information and communication technology (ICT) has a significant positive effect on students' learning motivation. In addition, social interaction between students and teachers and support from parents also contribute to increased motivation. This study provides recommendations for educators and policy makers to create a more supportive learning environment, especially in the use of technology to increase student motivation in the digital era.